2019
DOI: 10.3389/fpsyt.2019.00155
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Intervention to Improve the Health Related Quality of Life in Children and Young People With Serious Parental Mental Illness

Abstract: Introduction: Children and adolescents living with parental mental illness (CAPRI) are at increased risk of behavioral, social and educational difficulties, mental and physical health problems and have poorer quality of life (QoL). Adverse outcomes can extend into adulthood but are not inevitable. Recent policy and stakeholder consultation recognize the urgent need for interventions that extend beyond objective, service-led measures of health. Systematic evidence synthesis has demonstrated a lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…However, the extent to which these guidelines are implemented in practice is currently unknown and probably varies from region to region. Most importantly, future studies need to evaluate the implementation of such targeted home safety interventions in families with parental mental illness and identify the specific needs and experiences of these families 6061…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent to which these guidelines are implemented in practice is currently unknown and probably varies from region to region. Most importantly, future studies need to evaluate the implementation of such targeted home safety interventions in families with parental mental illness and identify the specific needs and experiences of these families 6061…”
Section: Discussionmentioning
confidence: 99%
“…Children of parents with psychotic disorders are at risk of emotional and behavioural difficulties during childhood [ 33 ] and psychopathology later in life [ 34 ]. Interventions currently exist to provide support to these children by explaining their parent’s illness [ 35 ], linking the family with a caseworker [ 36 ], and providing treatment for children’s own mental health difficulties [ 37 ]. However, before receiving support, these children must be accurately identified, and that information should also be shared between adult mental health services and other agencies [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These children would likely benefit from some respite from their home environments. Interventions have been developed, which aim to improve the quality of life and daily functioning in children affected by parental mental illness (Gellatly et al, 2019; Müller et al, 2019), and such preventative interventions for these children have been shown to reduce children's likelihood of developing a mental illness themselves (Lannes & Arnaud, 2021).…”
Section: Discussionmentioning
confidence: 99%